Pemetaan Pasar Tradisional Di Wilayah Pesisir Sebagai Pusat Perbelanjaan Masyarakat Kabupaten Bone Bolango - Melo, Ramla Hartini; Laudji, Mohammad Alfian; Setiasih Niode, Syarifah Fatimah; Kobi, Wiwin; Endang Saleh, Sri (Universitas Negeri Gorontalo, 2025)
Bone Bolango Regency, located in a coastal area, is known to have various traditional markets that function as centers of trade for the local community. These markets play a vital role in the local economy by providing places for traders to sell a wide range of commodities, from agricultural and fishery products to basic necessities. This study aims to develop a distribution map of traditional markets in the coastal area of Bone Bolango Regency using a mapping approach through a Geographic Information System (GIS). GIS serves as a highly useful tool in mapping these markets. The results show that the mapping of traditional markets in Bone Bolango Regency can be easily accessed through GIS. The integration of spatial and attribute data produces maps that are not only informative but also interactive. Data on market locations, infrastructure, and accessibility are visually presented.